The development and preliminary psychometric properties of the Values Wheel - O'Connor, Moira; Tennyson, A.; Timmons, M.; McHugh, L. (2019)
© 2019 Association for Contextual Behavioral Science Background: In Acceptance and Commitment Therapy (ACT), personal values function as motivational guideposts for behavior change and adaptive functioning. The continued empirical progress of this process-based therapy necessitates the development and evaluation of measures of values-directed behavior. This study reports on the preliminary psychometric properties of the Values Wheel: a new psychometric instrument designed and manufactured to provide an idiographic and weighted index of clients’ values-directed behavior. Method: One hundred fifty adults attended an assessment session on an individual basis to complete a values card sort task, Values Wheel and questionnaire measures of positive mental health, psychological distress and ACT processes. To investigate temporal stability, 39 participants completed two subsequent assessment sessions – each separated by a two-week interval. Results: The Values Wheel demonstrated evidence of temporal stability with large correlations between the scores obtained on the three occasions. Correlations with indices of valued living provided preliminary support for the measure's construct validity, whereas criterion-related validity was partially supported by correlations with positive mental health and stress. Conclusions: These findings provide preliminary support for the psychometric properties of the Values Wheel. Notwithstanding this study's limitations, the Values Wheel may hold potential as a measure of values-directed behavior with a broad scope of application in diverse contexts and languages.